IIe Biennale Internationale de la Gravure Cracovie 1968. - Wejman, Mieczyslaw; IIe Biennale Internationale de la Gravure Cracovie 1968 (Krakow, : Ministerstwi Kultury i Sztuki, 1968)
Akhrass, Gayass ; Aleksiun, Jan ; Alexanco, José Luis ; Alviani, Getulio ; Alves, Thereza Miranda ; Amano, Kazumi ; Amano, Kunihiro ; Amgalan, D. ; Andal, Michèle ; Anderle, Jiri ; Antes, Horst ; Apollonio, Marina ; Araki, Tetsuo ; Armagni, Alda Maria ; Assumcao-Souza, José ; Asgerisson, Bragi ; Avati, Mario ; Baldessin, George ; Babinski, Maciej Antoni ; Ballif, Yannick ; Banaszewski, Roman ; Bando, Soichi ; Barcellos ; Baranska-Bober, Joanna ; Bates, Pat Martin ; Bednarova, Eva ; Belgeonne, Gabriel ; Benjamin, Anthony ; Bergander, Rudolf ; Berkeley, Robert Stuart ; Bernet, Francisco Garcia ; Berni, Antonio ; Bertemes, Roger ; Bessoudo, Bess Ruth ; Bettiol, Zoravia ; Bhavsar, Natvar ; Böckman, Bengt ; van den Bogaert, Ilse ; de Bolle, Francis ; Bonnier, Alexandre ; Bonomi, Maria ; Boonen, Jac ; Boratynski, Antoni ; Borcic, Gogdan ; Borysowski, Stanislaw ; Breivik, Anne ; Bresciano, Miguel ; Broniek, Zofia ; Bru, Roser ; Brunovsky, Albin ; Buczynska, Ewa ; Bunsch, Franciszek ; Burkiewicz, Franciszek ; Caballero, Adela Allende ; Cabé, Carlos Alberto ; Canh, Duonc Ngog ; Caraceni, Bruno ; Carcan, René ; Carrion, Antonio Lorenzo ; Cecge, Zyndyi ; Cechova, Olga ; Cepelak, Ladislav ; Cedew, Rawsal ; Chew, Robert ; Chiaverini, Miria ; Chirnoaga, Marcel ; Chopra, Jagmohan ; Chrostowska, Halina ; Clave, Antoni ; Claesson, Rune ; Corneille ; Coudrain, Brigitte ; Coutu, Jack ; Cullom, Adrienne ; Cumic, Mihailo ; Cvorovic, Slavoljub Slavko ; Dabova, Zlatka ; Dalvit, Oskar ; Damski, Stefan ; Dannehl, Brigitte ; Danylewich, Morris John ; Dawski, Stanislaw ; Debenjak, Riko ; Degenhardt, Gertrude ; Deguide, Frédéric ; Detyniecki, Mieczyslaw ; Devayani ; Diederen, Jef ; Dorny, Bertrand ; Doudtchitzky, Dinora ; Doxat, Robert ; Dretler-Flin, Stefania ; etc.
Frans & Pools
boek